2021
DOI: 10.3390/ijms22158037
|View full text |Cite
|
Sign up to set email alerts
|

Design and Encapsulation of Immunomodulators onto Gold Nanoparticles in Cancer Immunotherapy

Abstract: The aim of cancer immunotherapy is to reactivate autoimmune responses to combat cancer cells. To stimulate the immune system, immunomodulators, such as adjuvants, cytokines, vaccines, and checkpoint inhibitors, are extensively designed and studied. Immunomodulators have several drawbacks, such as drug instability, limited half-life, rapid drug clearance, and uncontrolled immune responses when used directly in cancer immunotherapy. Several strategies have been used to overcome these limitations. A simple and ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 163 publications
0
14
0
Order By: Relevance
“…Compared to their linear counterparts, star polymers show enhanced drug loading content (DLC), drug loading efficiency (DLE), and longer circulation time. [104][105][106] As computational studies reveal, a simulated drug delivery system for water-soluble drugs with droplets containing nanoparticle liquid crystals in different shapes has demonstrated that drugs are concentrated in the core of star-shaped NPs (red color). In contrast, the ve star arms (blue color) do not carry drugs.…”
Section: Star-shaped Nanocarriersmentioning
confidence: 99%
“…Compared to their linear counterparts, star polymers show enhanced drug loading content (DLC), drug loading efficiency (DLE), and longer circulation time. [104][105][106] As computational studies reveal, a simulated drug delivery system for water-soluble drugs with droplets containing nanoparticle liquid crystals in different shapes has demonstrated that drugs are concentrated in the core of star-shaped NPs (red color). In contrast, the ve star arms (blue color) do not carry drugs.…”
Section: Star-shaped Nanocarriersmentioning
confidence: 99%
“…As excellent biocompatible materials, GNPs are efficient antigen and adjuvant delivery vehicles for inducing a cytotoxic T-cell response, can artificially present antigens, and can be functionalized to provide co-stimulation. GNP can bind with human DC to help activate cytokine production [ 97 ]. GNP demonstrates a high plasmonic effect, reduced cytotoxicity, and ability of diverse functionalization [ 98 , 99 ].…”
Section: Nanomaterials Enriching the Repertoire Of Immunotherapeutic ...mentioning
confidence: 99%
“…Immunotherapy for cancer refers to the treatment of cancer by activating the body's immune system with drugs to attack tumor cells through the body's natural immunity 294,295 receptor T cells), excitatory antibody receptors for costimulation, cancer vaccines, oncolytic viruses, and bisspecific antibodies 296,297 . Nanoparticles are often used to specifically deliver antigens, adjuvants, and therapeutic agents 298,299 . Nanoparticles themselves can also regulate immune microenvironment of tumors [300][301][302][303] .…”
Section: Immunotherapymentioning
confidence: 99%
“…296,297 Nanoparticles are often used to specifically deliver antigens, adjuvants, and therapeutic agents. 298,299 Nanoparticles themselves can also regulate the immune microenvironment of tumors. 300–303…”
Section: Combination Therapiesmentioning
confidence: 99%